Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/avsc.12653
|View full text |Cite
|
Sign up to set email alerts
|

Radiation use efficiency of the herbaceous layer of dry Chaco shrublands and woodlands: Spatial and temporal patterns

Abstract: Aims Monitoring rangeland above‐ground net primary production (ANPP) requires information on the variation of radiation use efficiency (RUE). We studied the spatial and temporal variations of RUE of the herbaceous layer (RUEH) in woodlands and shrublands and its association with grazing regime, environmental, and vegetation variables. Location We worked in the Arid Chaco (Argentina), an ecotone region between the Chaco and Monte phytogeographic provinces. Woody and herbaceous species coexist in variable propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…The results demonstrated that precipitation and temperature were the first and second most important variables, while nitrogen deposition also had a significant impact. The results in [84] also demonstrated that the temporal variability of NPP could be largely explained by the precipitation during growing seasons. Many others studies have also pointed out that precipitation and temperature directly affect the distribution and accumulation of primary production [48,75,79,82,92,94].…”
Section: Primary Productivitymentioning
confidence: 66%
See 1 more Smart Citation
“…The results demonstrated that precipitation and temperature were the first and second most important variables, while nitrogen deposition also had a significant impact. The results in [84] also demonstrated that the temporal variability of NPP could be largely explained by the precipitation during growing seasons. Many others studies have also pointed out that precipitation and temperature directly affect the distribution and accumulation of primary production [48,75,79,82,92,94].…”
Section: Primary Productivitymentioning
confidence: 66%
“…Zheng et al [76] also constructed a CASA model, which estimated FPAR based on the NDVI and proved a strong correlation between spring phenology and NPP in alpine grasslands. In addition, the NDVI time series were built by Blanco et al [84] using MODIS data to estimate FPAR by a linear model, and NPP was calculated by a LUE method. Gaffney et al [85] constructed the NDVI time series with high spatial and temporal resolution by fusing Landsat and MODIS data to fit the APAR for semiarid rangelands, and the above-ground NPP was estimated by a linear model similar to Equation (1).…”
Section: Primary Productivitymentioning
confidence: 99%